Saudi Arabia's 'Vision 2030' and Trump's second term: Between diverging interests and business relations - Stephan Roll; Antonia Thies (Stiftung Wissenschaft und Politik (SWP), 2025)
Saudi Arabia has mixed expectations ahead of Donald Trump's imminent second presidency. On the one hand, the royal family maintains close business relations with the president-elect and his entourage, which could lead to privileged access to the White House. On the other hand, Trump's Middle East policy, his confrontational stance towards China and his plans to increase domestic oil production could all jeopardise the kingdom's ongoing transformation under its ambitious "Vision 2030" development agenda. This presents opportunities for Germany and its European partners to step up cooperation with the kingdom, not least in order to advance their own strategic interests vis-à-vis Washington.
Keywords: 320; Saudi Arabia; "Vision 2030"; Donald Trump; Elon Musk; US Middle East policy; Germany; Saudi Public Investment Fund (PIF); Iran; regional stability; Israeli-Palestinian conflict; Benjamin Netanyahu; China; oil revenues; fracking industry; Petroleum Exporting Countries (OPEC)